Connectors for electrical and electronic equipment. Detail specification for two-way, shielded or unshielded, free and fixed connectors. Mechanical mating information, pin assignment and additional requirements for Type 1 copper LC style Part 1, (5th June 2020) - British Standards Institution,
No abstract available